Risk Factors for Prolonged Birth Interval in Modern Swine Farms in Vietnam - N. H. Nam; P. Sukon (Faculty of Animal Science, Bogor Agricultural University, 2022)
The present study aimed to investigate factors influencing the prolonged birth interval in swine, defined as a birth interval longer than 30 minutes. In total, 3380 piglets born from 239 Landrace x Yorkshire sows from 5 farms in the North of Vietnam were included in this study. The dependent variable was the prolonged birth interval, and independent variables included parity, gestation length, litter size, relative birth order, crown-rump length, birth weight, body-mass index, ponderal index, piglet’s gender, dead-born piglet, and oxytocin use. Important factors for the prolonged birth interval were determined by using Generalized Linear Mixed Models. The incidence of the prolonged birth interval was 14.5%. Crown-rump length (OR=1.09, 95% CI=1.06-1.14), birth weight (OR=1.06, 95% CI=1.02-1.09), and dead-born piglet (OR=1.98-2.08, 95% CI=1.38-2.97) were positively associated with the prolonged birth interval, while litter size (OR=0.90, 95% CI=0.96-0.94) negatively correlated with the prolonged birth interval. The incidence of prolonged birth interval decreased with an increase in relative birth order, bottoming at relative birth order of 40-80, and then increased to the end of parturition. The last piglets had the highest risk of experiencing prolonged birth intervals. This study indicated that prolonged birth interval in swine was common; therefore, careful farrowing supervision should be practiced to reduce stress in sows and piglets.